Bladder (ICRU) dose point does not predict urinary acute toxicity in adjuvant isolated vaginal vault high-dose-rate brachytherapy for intermediate-risk endometrial cancer - Sapienza, Lucas Gomes; Aiza, Antonio; Gomes, Maria José Leite; Chen, Michael Jenwei; Pellizzon, Antonio Cassio de Assis; Mansur, David B.; Baiocchi, Glauco (Journal of Contemporary Brachytherapy, 2015)
Purpose: High-dose-rate brachytherapy (HDR-BT) alone is an adjuvant treatment option for stage I intermediate-risk endometrial cancer after complete surgical resection. The aim of this study was to determine the value of the dose reported to ICRU bladder point in predicting acute urinary toxicity. Oncologic results are also presented. Material and methods: One hundred twenty-six patients were treated with postoperative HDR-BT 24 Gy (4 × 6 Gy) per ICRU guidelines for dose reporting. Cox analysis was used to identify variables that affected local control. The mean bladder point dose was examined for its ability to predict acute urinary toxicity. Results : Two patients (1.6%) developed grade 1 gastrointestinal toxicity and 12 patients (9.5%) developed grades 1-2 urinary toxicity. No grade 3 or greater toxicity was observed. The mean bladder point dose was 46.9% (11.256 Gy) and 49.8% (11.952 Gy) for the asymptomatic and symptomatic groups, respectively (p = 0.69). After a median follow-up of 36.8 months, the 3-year local failure and 5-year cancer-specific and overall survival rates were 2.1%, 100%, and 94.6%, respectively. No pelvic failure was seen in this cohort. Age over 60 years (p = 0.48), lymphatic invasion (p = 0.77), FIGO histological grade (p = 0.76), isthmus invasion (p = 0.68), and applicator type (cylinder × ovoid) (p = 0.82) did not significantly affect local control. Conclusions : In this retrospective study, ICRU bladder point did not correlate with urinary toxicity. Four fractions of 6 Gy HDR-BT effected satisfactory local control, with acceptable urinary and gastrointestinal toxicity.